2022
DOI: 10.3892/etm.2022.11155
|View full text |Cite
|
Sign up to set email alerts
|

miR‑146b‑5p promotes colorectal cancer progression by targeting TRAF6

Abstract: Increasing evidence highlights the multiple roles of microRNAs (miRs) in the tumorigenesis of colorectal cancer (CRC); however, the molecular mechanism, particularly the target of miR-146b-5p in CRC has not been fully elucidated. The present study aimed to elucidate the influence of miR-146b-5p via regulating tumor necrosis factor receptor-associated factor 6 (TRAF6) in CRC. The expression levels of miR-146b-5p and TRAF6 in CRC tissue and cells were determined by reverse transcription quantitative PCR and west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…was observed in previous study [19][20][21], but whether ePPMO-146b exerted equal or even stronger effects remained unclear.…”
Section: Eppmo-146b Inhibits Crc Cell Metastasis By Hampering Emtmentioning
confidence: 86%
See 2 more Smart Citations
“…was observed in previous study [19][20][21], but whether ePPMO-146b exerted equal or even stronger effects remained unclear.…”
Section: Eppmo-146b Inhibits Crc Cell Metastasis By Hampering Emtmentioning
confidence: 86%
“…Recently, some miRNA drugs have been approved to enter clinical trials on indications other than solid tumors, such as cutaneous T-cell lymphoma and Alport syndrome [37,38]. Many data have demonstrated a de nitive protumorigenic role of miR-146b in CRC, suggesting that ASO-miR-146b is feasible for developing a targeted drug [19][20][21]. To overcome the poor cellular uptake of oligonucleotide drugs, nanotechnology has been developed for miRNA or ASO delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that miR-146b-5p (miR-146b) significantly promoted epithelial–mesenchymal transition phenotypes through Smad4 in CRC cells [ 19 ]. An in vivo study has demonstrated that miR-146b may play a tumor-promoting role in establishment of CRC [ 20 , 21 ]. To therapeutically modulate miR-146b expression, we employed a synthetic anti-miR-146b ASO (PMO-146b) that is complementary to the mature miR-146b.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-146b-5p can play a pro-cancer or anti-cancer role in cancer progression. Shi et al [9] showed that miR-146b-5p could promote colorectal cancer development through targeting TRAF6. Ren et al [10] disclosed that miR-146b-5p is a cholangiocarcinoma inhibitor through targeting TRAF6 to repress proliferation and stimulate apoptosis of cholangiocarcinoma cells.…”
Section: Introductionmentioning
confidence: 99%